24. Antimicrobial Activity of Ant Plant (Myrmecodia sp.) Water Fraction to Escherichia coli and Salmonella sp. Growth - Roslizawaty Roslizawaty; Robbi Ghani; Maryulia Dewi; Darniati Darniati; T. Armanyah TR; Ginta Riady; Nuzul Asmilia (Universitas Syiah Kuala, 2019)
The aim of this study was to determine antimicrobial activity of sarang semut (Myrmecodia sp.) to Escherichia coli and Salmonella sp. growth using Kirby Bauer methode. This study used Completely Randomized Design one way pattern. Sample used was water fraction of sarang semut with concentration of 25% (P2), 50% (P3), and 75% (P4). Positive control was amoxycillin and negative control was Aquadest. Data were analyzed by Analysis of Varians (ANOVA). Average clear zone formed on Escherichia coli of P0, P1, P2, P3, and P4 were 0; 18,76; 5,96; 6,4; and 7,8 mm, respectively. Average clear zone formed on Salmonella sp. of P0, P1, P2, P3, and P4 were 0; 33,63; 7,73; 10,5; and 11,56 mm, respectively. ANOVA analysis showed there was correlation between extract concentration and inhibition zone on each culture of Escherichia coli and Salmonella sp. T test on P2, P3, and P4 showed that this extract had better antimicrobial effect on Salmonella sp. compared to Escherichia coli. In conclusion, water fraction of Myrmecodia sp. had capability to inhibit Escherichia coli and Salmonella sp. growth.